Analisis SWOT Pada UMKM Donat DS - Adinda C L Malawat; Tyna Yunita; Antonius T Nugroho; Ni P M P S Putri; Raeva S P Lestari; Raissyah Sudrajat (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
DS Donuts MSME is a culinary business whose main products are donuts and bakery items, with the potential to grow amid increasing public demand for ready-to-eat food products. In running its business, DS Donuts faces various internal and external factors that affect business sustainability. A SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats faced by the business. The analysis results show that the business's main strengths are distinctive product taste, affordable prices, quality ingredients, and good customer service. On the other hand, weaknesses include limited capital, less effective promotion, and limited production capacity. Opportunities that can be utilized include increasing public interest in bakery products, the development of digital technology as a marketing tool, and opportunities for collaboration with various parties. Meanwhile, threats come from high competition from similar businesses, changes in consumer preferences, and fluctuations in raw material prices. Based on the SWOT analysis, DS Donuts MSME needs to maintain product quality, increase digital marketing activities, carry out product innovation, and expand its marketing network to increase competitiveness and support sustainable business development.